"Splendid Isolation" as Trade Policy: Mercantilism and Crude Keynesianism in "the Capaldo Study" of TTIP - Matthias Bauer; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2015)
A recent study by Capaldo suggests that TTIP would have seriously negative consequences for trade, growth, income and employment in Europe. It has been given a surprising amount of attention, despite the fact that errs on the extreme side of trade estimates. Such serious flaws, however, beset the study, that its results should neither be regarded reliable nor realistic. The paper has been translated into several European languages and influential anti-TTIP campaign groups in Europe particularly distribute it. The use if the study and the flaws of the applied methodology give the impression that the results are constructed. Capaldo has chosen a model that is by and large a demand-driven model that does not makes efforts to capture the supply-side effects of trade, which are the effects that are proven to be the core positive effects of trade liberalisation. Equally problematic, the model is not designed to assess the effect on trade from trade agreements - in fact, the model is profoundly ill suited for such an exercise. No trade economist, regardless what school of thought he or she comes from, has ever used this model to make estimates of trade. The reason is simple: if a model cannot predict the effects on the flows and profile of trade as a consequence of trade liberalisation, it is of no use at all. And yet, to cover up the flaws of the model, Capaldo reinforces the problems and makes the model, and the resulting estimates of TTIP, even less reliable. In addition, despite the ownership of this model by a United Nations agency, access to it is denied and so is the possibility to replicate the model in order to check its predictive power and robustness. (...)
Keywords: 330